Colposcopic biopsy findings among women with either HPV‐16 only or HPV‐18 only who have normal cervical cytology. Issue 3 (6th September 2018) - Yalcin, Ibrahim; Sari, Mustafa E.; Sahin, Hanifi; Gultekin, Murat; Gungor, Tayfun; Meydanli, Mehmet M.
Abstract: Objective: To compare colposcopic biopsy results among women with normal cervical cytology who had positive test results for either HPV‐16 only or HPV‐18 only. Methods: A cross‐sectional study was conducted at Zekai Tahir Burak Women's Health Research and Training Hospital, Ankara, Turkey, between July 1, 2015, and October 31, 2017. Colposcopic biopsy results were compared among women in the HPV‐16 only (n=185) and HPV‐18 only (n=43) groups. Results: Women who had HPV‐16 only were more likely to be smokers than women with HPV‐18 only ( P =0.003). By contrast, women with HPV‐18 only were more likely to be aged at least 45 years than women who had HPV‐16 only ( P =0.038). High‐grade squamous intraepithelial lesions were detected more frequently in the HPV‐16 only group (51 [27.6%]) than in the HPV‐18 only group (4 [9.3%]; P =0.010). By contrast, no between‐group difference was found for the rate of invasive cervical cancer, which was detected in 1 (0.5%) woman in the HPV‐16 only group and 1 (2.3%) woman in HPV‐18 only group ( P =0.342). Conclusion: Although the risk of high‐grade squamous intraepithelial lesions was increased among women with HPV‐16 only, this finding did not influence the rate of invasive cervical cancer when compared with women in the HPV‐18 only group. Abstract : High‐grade squamous intraepithelial lesions were increased among women with normal cervical cytology and HPV‐16 only versus women with normal cervical cytology and HPV‐18 only.